Hubungan persepsi ibu tentang susu formula dengan pemberian susu formula Pada bayi usia 0-6 bulan - Gusli - Kurniawan; Widia - Lestari; Siti Rahmalia HD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The purpose of this study was to determine the relationship of maternal perception of infant formula to formula feeding in infants aged 0-6 months. This research was a analytic survey research. The research design used in this study was cross-sectional. The study was conducted in Puskesmas Sidomulyo Pekanbaru involved 30 mothers with infants aged 0-6 months. The sampling technique was accidental sampling. Data collection tool was a questionnaire that had been tested for validity and reliability. This study used univariate and bivariate data analysis. The results showed a significant relationship between maternal perception of infant formula to formula feeding in infants aged 0-6 months (P value 0.007 < α 0.05. It was recommended to health professionals providing counseling or guidance to the public on the effects of formula feeding in infants aged 0-6 months. Keywords: Infants 0-6 months of age, perception, formula milk, formula milk feeding